Methodological approach for the zoning of the rock fall hazard in lineal projects - Rendón-Rivera, Albeiro de Jesús; Vilaplana-Fernández, Joan Manuel (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2009)
In this communication it is showed a methodological approach for the zoning of the threat of rock falling, which may be applied in projects of lineal infrastructure or urban environments. It is based on a multicriteria analysis that is supported by a solid base of data and that integrated in Arc-Gis/Arc-Info by an index of threat factors like the delimitation of the corridors of block transit, geological-geomorphologic cartography, cartography of RMR index, cartography of the susceptibility, and the volumetric analysis of talus deposits amongst others, allows to calculate for each transit corridor the index of threat, príoritize achieving for a process of risk management in short, medium and long term. The above mentioned methodology was applied with good results in Vall de Nuria that is devoted to mountain tourism, located in the eastern Pyrenees of Spain, and has its access by rack railway that crosses a quaternary glacial valley modeled in gneisses, and whose railway line has been affected several times by rock falling, putting passengers in risk and affecting the commercial service.